Management of a feline gastric stromal cell tumour with toceranib phosphate: a case study. Issue 5 (23rd January 2020) - McGregor, O; Moore, AS; Yeomans, S
Abstract : Background: A fifteen‐year old, female spayed domestic longhaired cat was presented for a routine vaccination during which an incidental abdominal mass was palpated. After further inquiry, occasional vomiting was reported to occur once every few weeks to months, associated with no other gastrointestinal signs. Case report: Ultrasonography revealed a gastric mass. Histopathology and immunohistochemistry confirmed a CD117 positive, smooth muscle actin and desmin negative neoplasm, consistent with a gastrointestinal stromal cell tumour (GIST). Treatment was initiated with toceranib phosphate resulting in stable disease for over eighteen months, and the patient was still alive at the time of writing. Conclusion: GISTs are rare in cats and this is the first report of medical management of feline GIST using toceranib.